Leisure Boredom Scale: the Factor Structure and the Demographic Differences - Bulent Gurbuz; Erman Oncu; Feyza Kara (Selcuk University, 2014)
The purpose of this study was to investigate the reliability and validity of the Turkish version of the Leisure Boredom Scale (Iso-Ahola amp; Weissinger, 1990) for adults in Turkey. The second purpose was to investigate the differences based on demographic variables (gender, marital status, working sector) regarding leisure boredom. In total 312 employees from public and private sectors (167 female, 145 male) residing in Ankara participated in this study. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted to test the structural validity of the scale. EFA demonstrated that this scale yielded two subscales in the Turkish version. The first factor was named "boredom" and the second factor was named "satisfaction" by the participating researchers after reviewing the related literature and examining the factor structure of the scale. The scale consists of 10 items; the item factor loadings for the overall scale range between 0.38 and 0.83; and the Cronbach Alpha coefficient for the subscales was determined 0.72 for boredom and 0.77 for satisfaction in the final form of the scale. According to t-test results regarding the demographic variables, there was statistically significant difference in gender only in the ,satisfaction' subscale, and between women and men participants, with men participants having higher mean scores (p lt;.01). There was no significant difference in terms of marital status in total LBS and the subscales. Concerning the working sectors of the participants, the analysis showed significant differences in total LBS and the ,boredom' subscale between public and private sector's participants, with public sector's participants having higher mean scores than the latter (p lt;.01). In conclusion, the results of the research demonstrated that the Turkish adaptation of ,The Leisure Boredom Scale' can be used as a valid and reliable measurement tool to examine and evaluate the leisure boredom levels of Turkish adults. Another conclusion of the study worth noting is that there were significant differences between the different components of gender and working sector variables in terms of leisure boredom levels